'Race against race, immutable': Pound's fascist readings of Henry James. Issue 7 (2nd July 2020) - Barnes, David
ABSTRACT: Henry James is recognised as a major literary influence on modernism as it developed in Great Britain and the United States in the early decades of the twentieth century. Yet in the increasingly politicised writings of the modernist poet Ezra Pound, James stood for far more than literary experimentation. In Pound's writings, the novelist figured as an author peculiarly sensitive to notions of race and cultural integrity. In this essay, I explore Pound's creation of a 'Fascist' James, one whose battles on behalf of 'civilisation' came increasingly to signify for Pound a narrow, culturally exclusive and authoritarian world. By the late 1930s, James featured in Pound's Italian journalism as an ideal author for his 'Fascist Library'. With readings of Pound's early writings on James alongside in-depth analyses of the Pisan Cantos (1948), I argue that James's fictions of encounter between America and Europe became key to Pound's later vision of culture – a vision increasingly marked by its emphasis on the cultural and racial unity of Europe.